KONTRIBUSI BAITUL MAL TERHADAP PENDIDIKAN SANTRI DAN SISWA MISKIN - Murtadha (Jurnal Tarbiyah Almuslim, 2023)
For the realization of a good education, the things mentioned above cannot be avoided. So for this we need people who are responsible for education costs, such as parents/guardians, and there is responsiveness from the authorities such as Baitul Mal, social services, benefactors and so on. In the world of education, according to the author's observations, there are parents who are quite capable of paying for education, but their children are not able or are not interested, on the other hand, there are children who have the talent and interest in pursuing the highest education, but their parents do not have the ability, so for students like this needs to be paid attention to in order to achieve competent regeneration. Thus, the formulation of this article is: what are the criteria for students, how Baitul Mal contributes assistance to underprivileged students and students. This article uses a documentation study with a qualitative approach. This discussion focuses on Baitul Mal's contribution to education. This research needs to be highlighted because it is still relevant today, until the solution is found.